The effects of moderate-intensity continuous training and high-intensity interval training during a ketogenic diet on serum levels of irisin, PGC-1α and UCP1 in overweight and obese women - Behnam Behravan; Kazem Khodaei; Mohammadreza Zolfaghardidani (فیزیولوژی ورزش و فعالیت بدنی, 2024)
Background and Purpose: Nowadays, obesity has become a global challenge, and the use of strategies based on diet and exercise is recommended by experts and researchers for weight management. The aim of this study was to investigate the effectiveness of moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) during a ketogenic diet on the serum levels of irisin, peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α), uncoupling protein 1 (UCP1), and lipid profile of inactive overweight and obese women.Materials and Methods: Thirty-six inactive overweight and obese female students were selected and randomly divided into three groups (n=12) of ketogenic diet, ketogenic diet with MICT, and ketogenic diet with HIIT. The ketogenic diet with MICT group performed continuous running aerobic training with moderate intensity of 60-70% of the maximum heart rate for six weeks, three sessions per week, while, the ketogenic diet with HIIT group performed interval running at an intensity corresponsing to 85-95% of the maximum heart rate in 4-minute intervals. During this period all groups followed a low-carbohaydrate diet and the ketogenic diet group had no regular exercise. Blood samples were collected 48 hours before first training session and 48 hours after the last training session. Serum levels of PGC-1α, UCP1 and irisin were measured by ELISA technique and blood lipid profile was measured by colored enzyme assay method. Analysis of variance (ANOVA) with repeated measures and Bonferroni's post-hoc test were used for data analysis.Results: According to the results of ANOVA, the interaction effect of time in group was significant for the serum levels of irisin (p=0.011), UCP1 (p=0.003) and high-density lipoprotein (p=0.001). The results of the post-hoc test showed that the ketogenic diet group with HIIT had a significant increase in irisin (p=0.009) and high-density lipoprotein (p=0.001) compared to the ketogenic diet alone. There was no significant difference between the two training groups during ketogenic diet (p>0.05), though, within-group significant differences were detected in both training groups (p˂0.05). However, no significant between-group differences were observed in serum levels of PGC-1α, total cholesterol and low-density lipoprotein (p>0.05).Conclusion: Based on the findings of the present study, it seems that performing both types of continuous aerobic exercise with moderate intensity and intense interval along with the ketogenic diet is more effective than the ketogenic diet in terms of activating the browning pathways of adipose tissue and improving the blood lipid profile, in overweight and obese women. However, the ketogenic diet with HIIT showed better effectiveness than the ketogenic diet with MICT for irisin and high-density lipoprotein.